2012
DOI: 10.1038/ncomms2146
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the human-specific microRNA miR-941

Abstract: MicroRNA-mediated gene regulation is important in many physiological processes. Here we explore the roles of a microRNA, miR-941, in human evolution. We find that miR-941 emerged de novo in the human lineage, between six and one million years ago, from an evolutionarily volatile tandem repeat sequence. Its copy-number remains polymorphic in humans and shows a trend for decreasing copy-number with migration out of Africa. Emergence of miR-941 was accompanied by accelerated loss of miR-941-binding sites, presuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
111
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 60 publications
1
111
0
1
Order By: Relevance
“…4). The Primate and Homo sapience oncogenic miRNAs have retained their harmful regulatory interaction with target genes through their evolution because miRNA-mRNA interaction pave the way for the loss of newly formed miRNA and or causes the elimination of detrimental miRNA binding sites [16,26,27,28]. The expression of miR-195 and miR-497 were highly conserved in miRNA cluster and located at chromosome 17p13.1 and were down-regulated by DNA methylation and increased CpG methylation in breast cancer [29].…”
Section: Discussionmentioning
confidence: 96%
“…4). The Primate and Homo sapience oncogenic miRNAs have retained their harmful regulatory interaction with target genes through their evolution because miRNA-mRNA interaction pave the way for the loss of newly formed miRNA and or causes the elimination of detrimental miRNA binding sites [16,26,27,28]. The expression of miR-195 and miR-497 were highly conserved in miRNA cluster and located at chromosome 17p13.1 and were down-regulated by DNA methylation and increased CpG methylation in breast cancer [29].…”
Section: Discussionmentioning
confidence: 96%
“…The conservation allows an easy way to evaluate physiological effects of overexpression or loss-of-function of specific miRs in model organisms before human studies. Nevertheless, many human or primate specific miRs have been identified that play important roles in physiological and pathological pathways, such as cellular differentiation and cancer development (5557). It is likely that primate miRs have evolved to regulate species specific phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…High‐throughput next‐generation sequencing (NGS) emerged as a powerful tool to identify miRNAs from animals and plants (Calla & Geib, 2015; Guillem, Bastian, Maria‐Dolors, & Xavier, 2016; Nandety, Sharif, Kamita, Ramasamy, & Falk, 2015; Song et al., 2011; Wang et al., 2012; Wu et al., 2013). It has accelerated the pace of miRNA discovery from various animals and plants (Avesson, Reimegard, Wagner, & Söderbom, 2012; Burnside et al., 2008; Ge et al., 2013; Hu et al., 2012; Kang et al., 2012; Koh et al., 2010; Zhang et al., 2012). …”
Section: Introductionmentioning
confidence: 99%